2012
DOI: 10.1136/annrheumdis-2011-200391
|View full text |Cite
|
Sign up to set email alerts
|

Changes in matrix protein biochemistry and the expression of mRNA encoding matrix proteins and metalloproteinases in posterior tibialis tendinopathy

Abstract: ObjectivesAdult-acquired flat foot secondary to a dysfunctional posterior tibialis tendon (PTT) is often treated by surgical transfer of the flexor digitorum longus tendon (FDLT). In this study, the authors compared normal PTT, stage II dysfunctional PTT and replacement FDLT, aiming to define changes in collagen modification, glycosaminoglycan (GAG) and the expression of matrix and metalloproteinase mRNA.MethodsNormal PTTs were obtained from patients with no history of tendon problems. Samples of dysfunctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 46 publications
7
29
1
Order By: Relevance
“…The other histopathological changes observed in this study are similar to those reported in human tendinopathy [20, 27, 4952], and previous experimental studies using surgical transection or repetitive exercise models [24, 39]. Our previous studies also found that these histopathological changes were distributed widely throughout the tendon after a focal injury [22].…”
Section: Discussionsupporting
confidence: 89%
“…The other histopathological changes observed in this study are similar to those reported in human tendinopathy [20, 27, 4952], and previous experimental studies using surgical transection or repetitive exercise models [24, 39]. Our previous studies also found that these histopathological changes were distributed widely throughout the tendon after a focal injury [22].…”
Section: Discussionsupporting
confidence: 89%
“…Since we found unchanged type I collagen expression, decreased MMP-2 expression, and a trend toward an increased MMP-3 expression (P ϭ 0.07), it seems clear that the gene expression profile of the rat Achilles tendons subjected to 12 wk of running does not fit well with that of a tendinopathic tendon. In further support of this, we found decreased levels of VEGF and proteoglycan mRNA (fibromodulin and biglycan), which are thought to be elevated with tendinopathy (4,12,13,36,38). These mRNA results serve to underline the more fundamental finding of unchanged tissue histology, which clearly indicates that the training model does not induce Achilles tendinopathy.…”
Section: Regulation Of Gene Expressionsupporting
confidence: 69%
“…There are, however, some common findings in studies that have investigated differences in mRNA expression in tendinopathic tendon tissue vs. healthy tissue. These include an increased expression of collagen I and III mRNA (12,14,26,27), increased levels of MMP-2 mRNA (3,12,26,27) and decreased levels of MMP-3 mRNA (12,14,26,27,28). Since we found unchanged type I collagen expression, decreased MMP-2 expression, and a trend toward an increased MMP-3 expression (P ϭ 0.07), it seems clear that the gene expression profile of the rat Achilles tendons subjected to 12 wk of running does not fit well with that of a tendinopathic tendon.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%
“…The current study did not include analysis of the proteoglycan degrading enzymes ADAMTS4 and ADAMTS5 to determine if the accumulation of sGAGs correlated with altered expression and/or activity of these enzymes. Increased proteoglycan deposition in tendon disease correlates with ADAMTS5 knockout [55] and with its reduced expression in human tendinopathy [56]. It is intriguing that in equine suspensory ligament desmitis, chondroprogenitor cells appear responsible for elevated aggrecan synthesis and its accumulation may arise due to the inactivation of ADAMSTS5 despite its increased expression [57].…”
Section: Discussionmentioning
confidence: 99%